Procedural pain in children: a qualitative study of caregiver experiences and information needs - Kassi Shave; Samina Ali; Shannon D. Scott; Lisa Hartling (BMC, 2018)
Abstract Background Children experience multiple painful procedures when being cared for in emergency departments (EDs). Unfortunately, evidence-based interventions to manage such pain and distress are under-utilized across EDs. Caregivers are uniquely positioned and invested to advocate for the adaptation of such evidence into practice. Our objective was to gather information from caregivers of children experiencing procedural pain in the ED to inform the development of a novel, caregiver-focused knowledge translation (KT) tool. Methods The study design was qualitative description. Caregivers of children who underwent intravenous (IV) insertion or venipuncture in the pediatric ED at an urban tertiary care centre were interviewed. Thematic analysis was applied to the data. The TRanslating Emergency Knowledge for Kids (TREKK) Parent Advisory Group continuously informed this study, and provided input on interview guide development and piloting, data collection, analysis of the data, interpretation of the results, and development of next steps. Results Interviews revealed four major themes: 1) source of healthcare information; 2) delivering healthcare information; 3) communication with caregivers; and 4) procedure-related anxiety and long-term effects. Caregivers most valued receiving information directly from their healthcare provider. They also expressed that healthcare providers should direct information about the procedure to their child and identified strategies to involve children in their care. Caregivers wanted to be empowered to ask informed questions of their healthcare providers. Finally, caregivers reported negative experiences with procedures for their children, occurring mainly at non-pediatric centres. Conclusions We have identified core information needs for caregivers whose children are experiencing IV insertion or venipuncture. These results will form the foundation for the development of a KT tool that may empower caregivers to actively participate in their child's healthcare.